TAHU SERASI DALAM PRESPEKTIF MODAL SOSIAL (Studi Sosiologis Peran Modal Sosial Pada Usaha Tahu Serasi di Bandungan, Kabupaten Semarang) - Furi Adinda; Sri Suwartiningsih (Universitas Kristen Satya Wacana, 2015)
Amid the onslaught of foreign cultures, especially ready meals “fast food” causing further marginalization of the local culture. Building a community attitude to retaining local knowledge possessed, especially traditional food knows matching requires a very strong foundation on which the social capital. With the key issues above, this study aims to answer the main problem, that is explained about the role of social capital in the business Tahu Serasi in Kenteng, district Bandungan. This research used a qualitative approach and descriptive research method. The unit of observation is a businessman tahu serasi, marketeer tahu serasi, KUB, buyers and customers. The unit of analysis is the role of social capital in the business tahu serasi in the district Bandungan. Results of research on business know matching is the dimension of cooperation and trust. In the context of the social capital that the real economic transactions do not always think about the profitability and profit, but also to build a cooperative relationship. In the capital transformation, business activity know “tahu serasi” transformation of social capital into economic capital. Social capital is a strong foundation for business continuity tahu serasi to date. Keywords : Tahu Serasi, social capital, business continuity.